Relapsing Polychondritis Following Alopecia Areata - John C. Starr; Nidhika Taneja; George W. Brasher (Case Reports in Medicine)
A case of alopecia areata followed by relapsing polychondritis is presented. Similar cases from the literature are reviewed and speculation about the relationship of these diseases is offered. Although the occurrence of these diseases together could be coincidental, an association seems immunologically plausible. Thus, relapsing polychondritis might be an unusual systemic manifestation of alopecia areata.